Foreign Direct Investment and Economic Growth in Africa: Another Look from the WAEMU Region - M'baye, Cheick Kader (International Journal of Economics and Financial Issues, 2023)
Using panel cointegration and Granger causality techniques for the period 1994 to 2018, this article empirically explores the relationship between foreign direct investment (FDI) and economic growth in the West African Economic and Monetary Union (WAEMU). Contrary to the literature’s widely accepted opinion, we find no evidence of a causal relationship between FDI inflows and economic growth in the WAEMU region. This surprising result can be explained by the weakness of absorptive capacity factors as pointed out by the literature. However, we find contrary to the literature that the importance of absorptive capacity is a necessary but not sufficient condition to ensure the growth impact of FDI in these countries. The Null effect of FDI inflows on growth is also explained by the structural FDI sector-oriented puzzle observed in these countries. Sectors attracting the most FDI inflows are the ones that contribute the least to economic growth. Conversely, sectors contributing the most to economic growth are those which attract the least foreign capital. This finding provides crucial policy implications for the WAEMU region in terms of rethinking their FDI attractiveness policies in favor of more efficient, and inclusive economic growth.